PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA DEPOK : PENDAHULUAN, KAJIAN PUSTAKA, METODE, HASIL DAN PEMBAHASAN, PEMBAHASAN, KESIMPULAN, SARAN - Melianda, Nurkaya; Aprillia, Frida (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
BKPSDM of Depok City is an agency that acts as the executor of the regional government and is responsible for formulating technical policies in the field of personnel and providing service support for governance in regional personnel management as an effort to manage HR Management with leadership that motivates employees to work better and can fulfill organizational goals more efficiently and effectively. This study aims to determine the effect of leadership and work motivation on employee performance at BKPSDM Depok City partially and simultaneously. The research used statistical quantitative methods. The number of saturated samples in this study were 60 respondents from BKPSDM employees. The Data analysis techniques in this study used multiple linear regression methods, data management used SPSS Version 25. The test results show that: 1) partially leadership and work motivation on employee performance at BKPSDM Depok City,the result partial test Leadership (X1) has a coefficient regression of 5,504>2,002, then H0 is rejected and H1 is accepted, and work motivation (X2) has a regression coefficient of 10,471>2,002, then H0 is rejected and H2 is accepted, both variabels have a significance value < 0,05. So the results of the t (partial) test show that there is a positive and significant influence of the variabels Leadership (X1) and Work Motivation (X2) on employee Performance at affect employee performace at BKPSDM Depok City. 2) simultaneously leadership dan work motivation affect employee performace at BKPSDM Depok City, the test results were obtained from Fining>Frabel (53,941>3,16 and a significance < 0,05). Then the results of testing the f test (simultaneous) show that there is a positive and significant influence on the variables of leadership and work motivation simultaneously on employee performace at BKPSDM Depok City. Keywords: Leadership, Work Motivation, Employee Performance